Experiências (de um) docente no ensino de língua inglesa como língua adicional: uma cartografia do aprender surdo - Palaoro Junior, Olavo (Universidade Federal de São Carlos, 2026)
This study investigates the teaching of English as an additional language to deaf students in a municipal public school with a bilingual approach, focusing on these students' perceptions of the educational encounters that constitute their learning. The research starts from the understanding that language teaching for deaf students requires the recognition of a unique experiential matrix, constituted by Libras (Brazilian Sign Language) as the structuring language of deaf subjectivity. From this perspective, English is not understood as a third language but as an additional language, learned in contrast to Libras and traversed by linguistic, cultural, cognitive, and affective dimensions specific to deaf learning. The general objective of this research is to analyze the perceptions of deaf students regarding the educational process and the encounters that constitute their learning of English as an additional language, understood as an experience of invention and production of meaning in contrast to Libras (Brazilian Sign Language). Specific objectives include discussing the philosophical concepts of matrix language and additional language in English language teaching for the deaf students, in light of the Philosophies of Difference, problematizing ways of thinking about language as experience and not as representation; analyzing, based on existing research and productions, the dilemmas, advances, and conceptions that permeate English language teaching for deaf students, highlighting the tensions, challenges, and possibilities present in bilingual educational contexts, towards a multilingual and multimodal perspective; and promoting a cartography of the processes of subjectivation that are outlined in the perceptions of deaf students regarding the encounters experienced in learning English as an additional language, considering the conceptions of bilingualism and multilingualism as a theoretical basis for understanding such experiences.. The research is grounded in the philosophy of difference, especially the thoughts of Michel Foucault, Gilles Deleuze, and Félix Guattari, mobilizing the concepts of matrix of experience, matrix language, additional language, bilingualism, and multilingualism. The methodology adopted is cartography, understood as a method of data production that follows processes in motion and is constructed in the interstices of encounters. The empirical material consists of interviews with deaf students and the educational interpreter, as well as scenes from daily school life, analyzed through the mapping of molar, molecular, and escape lines. The analysis shows that learning English, when traversed by the centrality of Libras (Brazilian Sign Language) and by pedagogical practices sensitive to visual-gestural experience, displaces hegemonic models of language teaching and reveals the power of a multilingual, multimodal, and translinguistic perspective. By giving visibility to the perceptions of deaf students, the research contributes to rethinking the teaching of English as an additional language in bilingual contexts, affirming Libras (Brazilian Sign Language) as the primary language and learning as an ethical, political, and inventive process.
Experiences of a teacher in teaching English as an additional language: a cartography of deaf learning
Keywords: Educação de surdos; Ensino de inglês; Língua adicional; Libras; Cartografia; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade; 8. Trabalho Decente e Crescimento Econômico; 10. Redução das Desigualdades; 16. Paz, Justiça e Instituições Eficazes